Probing dual mode emission of Eu3 in garnet phosphor - Singh S.K.; Lee D.G.; Yi S.S.; Jang K.; Shin D.-S.; Jeong J.H. (My University, 2025)
Eu3 doped and Eu3, Yb3 co-doped Gd 3Ga5O12 phosphors have been developed by facile solid state reaction method which can be easily scaled-up in large quantity. The synthesis has been optimized to get a single phase material at 1300 °C. The phase and crystal parameters have been analyzed by using X-ray diffraction measurement. Photoluminescence excitation (monitored for the 5D 0 → 7F1 transition of Eu3) depicts that the active ion (Eu3) can be excited through direct excitation into 4f band of Eu3, through charge transfer band (Eu 3-O2-) excitation and also through the excitation into 8S7/2 → 6IJ intra f-f transition of Gd3 ion, which significantly all together cover a broad excitation region in 200-420 nm. In addition, in the presence of Yb3 ions, the emission is also achieved by near infrared excitation (976 nm), through a typical upconversion (UC) process. Thus, the material efficiently behaves as a dual mode emitting phosphor (emission is achieved both through normal fluorescence and through UC process). The conversion efficiency of silicon solar cells is only 15 of terrestrial solar energy for 200-400 nm region and also the sub-band gap energy (in infrared region) is lost as heat; therefore, this kind of dual mode phosphors may be used to overcome the above mentioned incomplete utilization of the solar spectrum and can open realm of new possibilities for energy harvesting. © 2013 AIP Publishing LLC.